Opportunities and barriers to translating the hibernation phenotype for neurocritical care - Drew, Kelly L.; Bhowmick, Saurav; Laughlin, Bernard W.; Goropashnaya, Anna V.; Tøien, Øivind; Sugiura, M. Hoshi; Wong, Ardy; Pourrezaei, Kambiz; Barati, Zeinab; Chen, Chao-Yin (Frontiers in Neurology, 2023)
Targeted temperature management is still standard of care for out of hospital cardiac arrest and neonatal hypoxic ischemic encephalopathy (HIE). Despite challenges to demonstrate efficacy in large clinical trials individual cases and experience of some clinicians argue against abandonment of this intervention. Mammalian hibernation is a gold standard of neuroprotective metabolic suppression, that if better understood might simplify TTM and improve overall efficacy. To translate hibernation or torpor for neurocritical care the technology must accommodate human vulnerability for cerebral ischemia/reperfusion injury. By contrast with humans, hibernating species tolerate ischemia/reperfusion without injury. Such tolerance limits risk of transitions into and out of torpor. Here we summarize what is known about reanimation or arousal from hibernation and discuss what this teaches us about how to safely reverse synthetic torpor in humans.